HARMONISASI HAK KEKAYAAN INTELEKTUAL DI ASEAN: Kendala Struktural dan Pilihan Pragmatis Pasca-2025 - Dinar Iftinan (Journal Publicuho, 2025)
The harmonisation of intellectual property (IP) systems in ASEAN remains a central challenge for deepening regional economic integration, particularly as the ASEAN IPR Action Plan 2016–2025 comes to a close and a new roadmap is being formulated. This paper examines the structural obstacles and pragmatic opportunities that shape IP harmonisation in the post-2025 transition period. Using a qualitative approach that draws on document analysis, primary ASEAN legal instruments, national IP office reports, and WIPO databases, the study applies a causal tracing process (CPT) to identify the causal sequences influencing regional IP cooperation. The findings show that two internal factors, the ASEAN Way and persistent development gaps among member states, continue to hinder legally binding harmonisation. However, external pressures from international regimes, including the RCEP IP Chapter, global WIPO treaties, and technical cooperation from the EU, Japan, and WIPO, have emerged as the most significant drivers of de facto harmonisation. These external mechanisms provide higher, enforceable standards and support institutional capacity-building, enabling convergence despite the limitations of ASEAN’s consensus-based framework. This paper concludes that ASEAN is moving toward a pragmatic model of IP harmonisation centred on system connectivity, capacity strengthening, and alignment with global rules rather than the creation of a unified regional IP system.